(untitled) (Annals of Medical Research, 2021)
Aim: The aim of our study was to evaluate the clinical results of arthroscopic repair and partial meniscectomy in the patients who had with meniscal tear.Material and Method: A total of 113 patients who were admitted to our clinic for meniscal tear between 2009 and 2017 were included in our study. Sixty one patients who underwent arthroscopic meniscal repair and 52 underwent partial meniscectomy. All inside meniscal repair technique was used for all meniscal repairs. Clinical assessments included physical examination findings, Lysholm score, the IKDC score and visual analog score(VAS). Barret criteria were used for the clinical assessment of healing status.Results: The patients who underwent meniscal repair, 54 (88.5%) were male 7 (11.5%) were female. The mean age was 32 (19- 45) years. Our mean follow-up period was 47 (range; 24-109) months. Number of patients underwent only meniscal repair was 29 and concurrent anterior cruciate ligament reconstruction was 32. According to the Barret’s criteria’s patients had 18% surgical failure. The patients who underwent partial meniscectomy33 were male 19 were female. Our mean follow-up period was 29.5 (range; 24-101) months. Eight patients (15.4%) had surgical failure. IKDC, Lysholm and VAS scores were statistically significantly improved postoperatively both in repair and partial meniscectomy groupConclusion: Meniscus repair should be performed whenever possible independent from age of patient. When repair is not possible, partial meniscectomy also have good results at least in short term follow-up.